2004
DOI: 10.1093/toxsci/kfh176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural and Synthetic Estrogens and Various Environmental Contaminants on Vitellogenesis in Fish Primary Hepatocytes: Comparison of Bream (Abramis brama) and Carp (Cyprinus carpio)

Abstract: Interaction of environmental estrogens with the estrogen receptor (ER) has been shown in various fish species. Our objective was to compare the sensitivity of bream (Abramis brama) to (xeno-)estrogens with that of the carp (Cyprinus carpio), by measuring the effects of 17beta-estradiol (E2), estrone (E1), ethynylestradiol (EE2), bisphenol A (BPA), nonylphenol (NP), methoxychlor (MXCL), and halogenated aromatic hydrocarbons (HAHs) such as polychlorinated biphenyls (PCB126, PCB118), 2,3,7,8-tetrachlorodibenzo-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 34 publications
6
24
0
Order By: Relevance
“…of six replicate samples from four different male fish. Significant differences between individual chemicals and corresponding co-exposure group were determined using student's t-test and are indicated by *P < 0.05 and **P < 0.01. was measured in medium using an ELISA method reported a calculated 48-h EC 50 for E2 of 0.3 M (Rankouhi et al, 2004). This value is comparable to our study, but much less than the value determined for rainbow trout (Oncorhynchus mykiss) (EC 50 = 1.8 nM) (Jobling and Sumpter, 1993), indicating that there is pronounced variability in EC 50 values among fish species.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…of six replicate samples from four different male fish. Significant differences between individual chemicals and corresponding co-exposure group were determined using student's t-test and are indicated by *P < 0.05 and **P < 0.01. was measured in medium using an ELISA method reported a calculated 48-h EC 50 for E2 of 0.3 M (Rankouhi et al, 2004). This value is comparable to our study, but much less than the value determined for rainbow trout (Oncorhynchus mykiss) (EC 50 = 1.8 nM) (Jobling and Sumpter, 1993), indicating that there is pronounced variability in EC 50 values among fish species.…”
Section: Discussionsupporting
confidence: 81%
“…However, the male liver is capable of synthesizing and secreting VTG in response to exogenous estrogen stimulation. Thus, induction of VTG in male fish hepatocytes has been utilized for chemical screening or environmental monitoring for estrogenic substances and is considered a reliable biomarker for exposure to environmental estrogens or estrogenic properties of xenobiotics (e.g., Sumpter and Jobling, 1995;Smeets et al, 1999;Navas and Segner, 2000;Rankouhi et al, 2002Rankouhi et al, , 2004Xie et al, 2005a,b;Letcher et al, 2005; for a review, see Navas and Segner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Species differences in response to E 2 have also been reported for in vitro induction of Vtg protein using primary cultures of male fish hepatocytes. The EC50s of E 2 in the hepatocytes of freshwater bream (Abramis brama) and common carp (Cyprinus carpio), both members of the cyprinid family, were 1.9 and 0.3 mM, respectively [31], whereas the hepatocytes of rainbow trout exhibited approximately half the maximum response at 1 to 10 nM of E2 [32]. In contrast, the effects of BPA in the present study are comparable to those reported in the literature.…”
Section: Vtg Gene Transcriptionsupporting
confidence: 81%
“…7,8) It has been reported that biodegradation of alkylphenol ethoxylates and alkylphenols stimulates production of biomarkers of estrogenic activity in male fish. 5,9,10) Many researchers have a great interest in oxidoreductases such as tyrosinase, [11][12][13][14][15] laccase, [16][17][18] and peroxidase, [19][20][21][22][23] because their industrial potentials are recognized in degradation and detoxification of recalcitrant environmental pollutions. The potential advantages of the enzymatic treatment include operation at low concentrations over wide pH and temperature ranges and the easy control process.…”
mentioning
confidence: 99%